KONSEP KREATIVITAS GARIN NUGROHO DAN KETERLIBATANNYA DALAM PERFILMAN DI INDONESIA - Novianto, Wahyu (Acintya, 2016)
Garin Nugroho is regarded as a film director who managed to put the local culture in the midst of global cultural dominance. Garin is also as one of the few directors in various parts of the world who do not like to repeat expressions. In every of his film works, Garin is capable of doubling his role asscreenwriter as well as a producer. Garin Nugroho’s selection of creative attitude is unique if juxtaposed with other Indonesian cinematographer-filmmaker. Therefore, it is interesting to examine about the creativity concept of Garin Nugroho and his involvement in the film industry in Indonesia.In regard to review on these issues, the theory of creativity is used to observe the creative attitudes and the ideas that underlie Garin’s movie creation process. The data that were used to reveal matterswere the three films of Garin Nugroho that entitledSurat Untuk Bidadari, Bulan Tertusuk Ilalang, and Opera Jawa. The data was obtained through the data collection techniques that include documentation, literature, and interviews. The result of this research shows that through the work of his movies, Garin attempted to reveal thatthere is harmony and balance in position between the local and the global value,where the selection of creative attitude shows a spirit of multiculturalism. Garin’s animating spirit of multiculturalism is not only demonstrated through his work, but also on his creative actions during the process of creating a movie. In this case, Garin is not only as a film director, but he is also as a humanist.Keywords: creativity, movie director, movies.